Considering weights in real social networks: A review - Bellingeri, M.; Bevacqua, D.; Sartori, F.; Turchetto, M.; Scotognella, F.; Alfieri, R.; Nguyen, N. K. K.; Le, T. T.; Nguyen, Q.; Cassi, D. (Frontiers in Physics, 2023)
Network science offers powerful tools to model complex social systems. Most social network science research focused on topological networks by simply considering the binary state of the links, i.e., their presence or absence. Nonetheless, complex social systems present heterogeneity of the link interactions (link weight), and accounting for this heterogeneity is mandatory to design reliable social network models. Here, we revisit the topic of weighted social networks (WSNs). By summarizing the main notions, findings, and applications in the field of WSNs, we outline how WSNs methodology may improve the modeling of several real problems in social sciences. We are convinced that WSNs may furnish ideas and insights to open interesting lines of new research in social sciences.